“HUKUM PERNIKAHAN LAKI-LAKI MUSLIM DENGAN PEREMPUAN NON MUSLIM (Studi Analisis Maqâshid Al-Syarî’ah terhadap Pendapat Muhammad Rasyîd Ridhâ dan Fatwa Majelis Ulama Indonesia)” - Fauzan Alfajri; Firdaus Firdaus (UIN Imam Bonjol Padang, 2020)
This research was motivated by differences of opinion between Muhammad Rasyîd Ridha and the Indonesian Ulema Council No. 05 / Kep / Munas II / MUI / 1980 concerning the Law of Muslim Men Marrying Non-Muslim Women. In the opinion of Muhammad Rasyîd RidhâAhl al-Kitâb are those who have a holy book that is believed to have been sent down by God, marrying Ahl al-Kitâb is permissible. On this basis it is permissible to marry a non-Muslim woman Ahl al-Kitâb. While marrying an idolatrous woman is haram, the idolatrous woman in question was an Arabic idolatrous at the time when the Qur'an was revealed. Meanwhile, according to the Indonesian Ulema Council, marrying a woman from Ahl al-Kitâb, there are differences in the opinion of the scholars, in line with that it is haram to marry a non-Muslim woman. There are two things that form the problem of this thesis. First, what are the factors that cause differences in opinion of Muhammad Rasyîd Ridhâ and the Indonesian Ulema Council. Second, what is the opinion of Muhammad Rasyîd Ridhâ and the Fatwa of the Indonesian Ulema Council in terms of maqâshid al- syarî'ah ?. This research is a research library (library research) because the data needed for the preparation of this scientific work are contained in primary sources in the form of Tafsir al-Manar, a collection of Fatwa Muhammad Rasyîd Ridhâ and a collection of Fatwas from the Indonesian Council. In addition, the secondary sources of this study were taken from the literature related to inter-marriage. After the data was collected, the writer classified and analyzed it by using the inductive method. The research findings are first, the cause of the difference in opinion between Muhammad Rasyîd Ridhâ and the Fatwa of the Indonesian Ulema Council is different in understanding the argument. The argument used by Muhammad Rasyîd Ridhâ is the zhahir verse of QS al-Maidah verse 5, while the Indonesian Ulama Council because there is a difference in ulama, the Indonesian Ulama Council chose an opinion that is forbidden because it considers the harm to be greater than the benefits. The argument used by the Indonesian Ulema Council is mashlahah dharûriyah. Second, the opinion of Muhammad Rasyîd Ridhâ which allows marrying non-Muslim women (Ahl al-Kitâb) by adhering to zahirnash in line with maqâshid al-syarî'ah, in this case there is one method of knowing the meaning shari 'namely bi zhawahiri al-nushush (text). Keywords: Nikah, Maqâshid al-Syarî'ah', Muhammad Rasyîd Ridhâ, Indonesian Ulema Council.